Look at the Chain Rule formula with a visual explanation of how it works: PS

tapetivk 2021-11-11 Answered
Look at the Chain Rule formula with a visual explanation of how it works:
(h(x))=(g(f(x)))=g(f(x))f(x)
g(f(x))-outside function
(f(x))-inside function
g(f(x))-derivative of the otside at f(x)
f(x)-derivative of the inside
Now, explain what happens in regards to calculating the derivative, if f(x) is also a composite function.
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

Kathleen Ashton
Answered 2021-11-12 Author has 15 answers
Step 1
Let f(x) also be a composite function
f(x)=p(q(x))
h(x)=g(f(x))=g(p(q(x)))
Using chain rule
h(x)=g(p(q(x))p(q(x))q(x)
=g(f(x))p(q(x))q(x)
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2022-06-22
I have a linear first order ordinary differential equation
d y d x + tan ( x ) y = 2 cos 2 x sin x sec x
with an initial condition as y ( π 4 ) = 3 2
My integrating factor μ ( x ) = sec x
After multiplication with the integration factor what I get is:
( s e c x   y ) = s i n 2 x s e c 2 x
or
( s e c x   y ) = 2 s i n x c o s x s e c 2 x
If I use the first equation I get:
y ( x ) = 1 2 c o s 2 x t a n x + c s e c x
and using the second equation I get:
y ( x ) = s i n 2 x t a n x + c s e c x
2   s i n x   c o s x   d x = 2 s i n 2 x 2 = s i n 2 x
with the first equation I get c=7 and second equation I get c = 13 2 .
It is a very simple differential equation but when I solve it I get two different answers. Is this ok?
asked 2022-05-27
I was trying to compute the solution for the following differential equation:
x ( 2 x 2 y l o g ( y ) + 1 ) y = 2 y
As I couldn't get anywhere I checked the hints in the textbook which are the following:
Reverse the way of thinking, namely view x as a function and y as a variable, considering that
y = d y d x = 1 d x d y => y = 1 x . Then it goes to say that the equation now becomes
x x 2 y = l o g ( y ) x 3
This final equation is obviously simple enough to solve, but how on Earth did they arrive there?
asked 2021-12-28
Obtain the Differential Equation from the family of ellipses centered at (h,k) whose semi-major axis is twice the semi-minor axis.
asked 2022-02-10

Find the Laplace Transform of: 5sin(3x)-17e-2x

asked 2020-11-09
Solve the third-order initial value problem below using the method of Laplace transforms
y2y"21y18y=18
y(0)=2
y(0)=7
y"(0)=95
asked 2021-03-04
Find the Laplace transformation (evaluating the improper integral that defines this transformation) of the real valued function f(t) of the real variable t>0. (Assume the parameter s appearing in the Laplace transformation, as a real variable).
f(t)=2t24cosh(3t)+et2
asked 2022-03-22
Find the solution of the following initial value problem:
x(t)7x(t)+10x(t)=0, x(0)=2, x(0)=3